Impact of investor’s behavior on investment decision Making: a survey on Colombo stock exchange, Sri Lanka - Balagobei, S. (South Eastern University of Sri Lanka, 2019)
Traditional finance has always presumed that investors are rational in their decision making process in the stock market about risk return trade-offs and maximizing utility. However, behavioral finance studies revealed that human beings do not behave as rationally as economists suppose as their decisions at times are affected by various factors. The objective of this study is exploring the investor’s behaviour influencing investment decision making at Colombo Stock Exchange. As there are limited studies about behavioral finance in Sri Lanka, this study is expected to contribute significantly to the development of this field in Sri Lanka. To achieve the objective, the questionnaires are distributed to a sample size of 100 individual investors who are involved in the Colombo stock Exchange. The collected data are analysed by using statistical techniques including factor Analysis. The result shows that there are four behavioral factors affecting the investment decisions of individual investors at Colombo Stock Exchange which are Herding, Heuristics, Prospect and Market. Most of the variables from all factors have moderate impacts whereas anchoring variable from heuristic factor has high influence and choice of stock variable from herding factor has low influence on investment decision making.
Keywords: Behavioral finance; Investor’s behaviour; Investment decision making